Implementasi Kebijakan Pembangunan Jalan pada Dinas Bina Marga Kabupaten Kuningan - Astuti As; Heriyani Agustina; I Machmud (Jurnal Ilmiah Publika, 2014)
ABSTRACT The author poured this essay writing with the title "Implementation of Road Construction Policy in Kuningan Bina Marga Office.  The problems that arise whether the implementation of road development policy in the Department of Highways District Kuningan not optimal. The objectives of this research are: (1) how Implementation of Road Construction Policy in Bina Marga Office of Kuningan Regency, (2) what factors influence the policy of Road Construction in Bina Marga Office of Kuningan Regency, (3) any obstacles faced in Implementation of Policy Implementation of Road Development at Bina Marga Office of Kuningan Regency. This study used qualitative research methods. Qualitative research method is the method used in natural object condition. The theory used in this research is George Edward III theory, which are: (1) communication, (2) sources, (3) disposition or attitude, (4) bureaucracy structure. The result shows that the Implementation of Road Construction Policy in Bina Marga Office of Kuningan Regency has not been optimally caused by many problems due to many obstacles such as delay of road construction fund delayed and can mempperlambat the process of development of the road, the attitude of the executing officers less responsible and less knowledge of the executing officers on the field so that road construction is not optimal yet.